Ownership Concentration and the Determinants of Capital Structure in Latin America (2008)
In this paper we study the capital structure determinants of Latin American firms using a comprehensive sample from 1996 to 2005 covering seven countries. We argue that ownership control is important for capital structure decisions in Latin America, where firms present a higher ownership concentration. We find a U-shape relation between ownership concentration and leverage. When ownership concentration is low its effect on leverage is negative, and when ownership concentration is high its effect on leverage is positive. This U-shape relation is consistent with the argument that ownership-concentrated firms avoid equity issuing because they do not want to share or to lose control, and this effect is contrary if the ownership structure has enough dispersion and losing control is not an issue. Consistent with the control argument, we also find that firms with more growth opportunities exhibit higher leverage. In addition, and consistent with previous literature on developed countries, we find that other factors that do not proxy for ownership control are important determinants of leverage. Firms that are larger, with more tangible assets, and that are less profitable are also more leveraged.